2009
DOI: 10.1091/mbc.e08-07-0759
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Deacetylase 4/Myogenin Positive Feedback Loop Coordinates Denervation-dependent Gene Induction and Suppression

Abstract: Muscle activity contributes to formation of the neuromuscular junction and affects muscle metabolism and contractile properties through regulated gene expression. However, the mechanisms coordinating these diverse activity-regulated processes remain poorly characterized. Recently, it was reported that histone deacetylase 4 (HDAC4) can mediate denervation-induced myogenin and nicotinic acetylcholine receptor gene expression. Here, we report that HDAC4 is not only necessary for denervation-dependent induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 46 publications
9
127
1
Order By: Relevance
“…Dach2 and Hdac9 are transcriptional corepressors that are highly expressed in innervated muscle and decrease following muscle denervation (Méjat et al, 2005;Tang et al, 2009). Using two models of nerve injury we show that Dach2 and Hdac9 reduce the rate of muscle reinnervation.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Dach2 and Hdac9 are transcriptional corepressors that are highly expressed in innervated muscle and decrease following muscle denervation (Méjat et al, 2005;Tang et al, 2009). Using two models of nerve injury we show that Dach2 and Hdac9 reduce the rate of muscle reinnervation.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have shown Dach2 and Hdac9 repress Myog expression and that Myog regulated the expression of genes that are associated with endplate formation, like those encoding nAChRs and Musk (Méjat et al, 2005;Macpherson et al, 2006;Tang et al, , 2009. Interestingly, miR206, a gene previously shown to participate in endplate reinnervation (Williams et al, 2009) is also regulated in a Dach2/Hdac9-dependent manner (Fig.…”
Section: Myog Stimulates Muscle Reinnervationmentioning
confidence: 76%
See 2 more Smart Citations
“…The potential for using HDAC inhibitors to treat ALS and other neuromuscular diseases is of great interest." 4,5 Hot for HDACs There are no disclosed class IIa-specific HDAC inhibitors in the clinic. Indeed, companies contacted by SciBX suggested the reason is not because they are hard to develop but rather that they have been a target class in search of an indication.…”
Section: Analysis Targets and Mechanismsmentioning
confidence: 99%